Student Interest in Student Savings Products at BPRS HIK Parahyangan Indramayu Branch - Annita Widiastuti; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2025)
Savings products for students at BPRS HIK Parahyangan, aims to determine how much interest students have in student savings. Student savings are savings for students issued nationally by banks in Indonesia with easy and simple requirements and attractive features. This Student Savings savings product uses the wadiah contract. The background of this research on student savings products is due to the tight competition between student savings products at BPRS HIK Parahyangan and student savings products at other Islamic Banks. This study uses a qualitative approach that is descriptive in nature. While this type of research is conducted with field research. data collected from interviews, as well as primary and secondary data. Based on the results of this study conducted by the author, it can be seen that among students there are still many who are not familiar with BPRS HIK Parahyangan Indramayu Branch, still lack interest in saving at BPRS HIK Parahyangan Indramayu Branch, Still Lack of Understanding of Student Savings Products, Lack of public attention to student savings promotions, still many who do not fully trust BPRS HIK Parahyangan Indramayu Branch.